2001
DOI: 10.1890/0012-9658(2001)082[2381:witorb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Observed Relationship Between Species Richness and Productivity?

Abstract: Understanding the relationship between species richness and productivity is fundamental to the management and preservation of biodiversity. Yet despite years of study and intense theoretical interest, this relationship remains controversial. Here, we present the results of a literature survey in which we examined the relationship between species richness and productivity in 171 published studies. We extracted the raw data from published tables and graphs and subjected these data to a standardized analysis, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

62
1,113
18
11

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,399 publications
(1,204 citation statements)
references
References 64 publications
62
1,113
18
11
Order By: Relevance
“…See Table 1 for plot location abbreviations richness increases monotonically with productivity at a cross-continental scale. This finding agrees also with the results of an earlier meta-analysis on the productivitydiversity relationships (Mittelbach et al 2001), which found monotonically increasing richness along productivity gradients typically at large spatial scales across climates, whilst at smaller scales within the same climate zone the relationship is known to be mostly unimodal (Michalet et al , 2006. At the same time, we found no evidence for the hypothesis that the intensity of facilitative interactions wanes at the most extreme levels of abiotic stress (Michalet et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…See Table 1 for plot location abbreviations richness increases monotonically with productivity at a cross-continental scale. This finding agrees also with the results of an earlier meta-analysis on the productivitydiversity relationships (Mittelbach et al 2001), which found monotonically increasing richness along productivity gradients typically at large spatial scales across climates, whilst at smaller scales within the same climate zone the relationship is known to be mostly unimodal (Michalet et al , 2006. At the same time, we found no evidence for the hypothesis that the intensity of facilitative interactions wanes at the most extreme levels of abiotic stress (Michalet et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…1b). This local-scale effect (sensu Mittelbach et al 2001) was driven by differences in Symbiodinium OTUs in O. annularis, with A3 only found at Tektite and D1a/D2 dominating at John's Folly ( Fig. 1; Supplementary Material 4).…”
Section: Partitioning Of Symbiodinium Otus By Host and Microhabitatsmentioning
confidence: 99%
“…Past observations and models drawn primarily from the plant ecology literature suggest that a unimodal diversity -productivity relation is ubiquitous (Rosenzweig 1992 ;Huston & Deangelis 1994 ). Recent reviews, however, showed that other types of relations without defi nite maxima (linear increase or decrease) can be equally as common (Mittelbach et al 2001 ). For our analysis, estimates for surface primary productivity were obtained Map of the location of datasets used in analyses of depth -diversity trends; see Table 5.1 for a description of the datasets.…”
Section: Expected D Epth -D Iversity T Rends and P Rocessesmentioning
confidence: 99%